Avaliação dos efeitos de nanotubos de carbono de múltiplas paredes funcionalizados e não funcionalizados na viabilidade e motilidade de Rhizobium tropici - Miriã Dayane de Souza Almeida (2019)
Among the many challenges facing nanotechnology is the understanding of how nanomaterials interfere with human health and environmental safety issues. Nanoecotoxicology is the branch of toxicology that is willing to evaluate and discuss these issues. At present, the studies focus mainly on the determination of the survival rate of test organisms in the presence of nanomaterials, as well as on analyzes of possible toxic effects in laboratory models, such as cells in culture. Among the different environments of interest, the aquatic environment is the most studied, being the microbiota of the soil one of the least approached. The objective of this work was to evaluate the effects of carbon nanotubes of multiple walls (MWCNT-COOH and MWCNT-NF) on the survival and motility of Rhizobium tropici in the search for an alternative model for the study of the effects of nanomaterials in the soil and the use of these materials in agricultural applications. For this, the analysis of the total number of cells after the exposure to the carbon nanotubes by measuring the optical density, and the evaluation of the cellular viability by means of counting of colony forming units in plates were carried out. In this way, growth curves were determined at different concentrations of nanomaterials. The results showed that the presence of MWCNT-NF and MWCNT-COOH at concentrations of 20mg/L; 15mg/L; 12.5mg/L; 7.5mg/L and 5mg/L, did not significantly affect the growth of R. tropici in vitro. Motility tests, however, showed interesting results, demonstrating that these materials interfere in the bacteria motility, since a higher CFU / mL count was recovered in areas with absence of carbon nanotubes.